Gamma Radioactivity levels of Rocks and Soils and Their Corresponding External Exposure in Navy Quarry Site, Abeokuta, South-West, Nigeria - Okedeyi, A.S; Arowolo, T.A; Gbadebo, A.M; Techokosa, P (Asian Journal of Applied Science, 2020)
Asian Journal of Applied Science